PENGARUH LATIHAN PLYOMETRIC TERHADAP HASIL TOLAK PELURU PADA ATLET LAMPUNG - Widiyatno Widiyatno; Wiyono Wiyono; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2017)
Objectives would like to be achieved in this study is to determine the effect of plyometric exercises to increase the results of shot-put of Lampung athlete. The research method used is experiment method research with 5 Lampung shot-put athletes as the population. The sampling technique used is the sample population. Data analysis test results early and late effects of plyometric exercises to improve the shot put results using